Design of a Simple and Practical Nanosystem Coordinates Tumor Targeting and Penetration for Improved Theranostics. Issue 2 (21st October 2018) - Xiang, Zhichu; Yang, Xiaoliang; Jiang, Gexuan; Fan, Di; Geng, Lingling; Wang, Hao; Hu, Zhiyuan; Fang, Qiaojun
Abstract: A novel amphiphilic peptide PA (APPA) containing two functional motifs is designed to coordinate the targeting to integrin αvβ3 and neuropilin‐1(NRP‐1) on cell membrane. The cooperation of the two motifs fulfills the penetration of APPA‐based nanosystem deep into tumor tissue and accumulates there. The APPA can be easily synthesized and self‐assembled into spherical nanoparticles in the presence of doxorubicin (DOX) (PAD), or can be used for construction of fluorescent nanoprobe in the presence of DiR (PA‐DiR). In vitro and in vivo studies demonstrate that the self‐assembled PAD and PA‐DiR nanosystems show a surprisingly high affinity for and penetration into αvβ3 and NRP‐1 positive tumors. The PA‐DiR nanoprobe can be specifically recruited to 4T1 xenograft tumors. The signal of PA‐DiR enriched in the tumor was more than 10 times higher than that of the negative control PC‐DiR. The high affinity and specificity of the PA‐DiR nanoprobe in in vivo fluorescence imaging, the profound therapeutic efficacy of PAD nanosystem in solid tumor models, and the low toxicity of APPA‐based nanosystem demonstrate the great potential of this well‐designed and simple nanosystem for application in the diagnosis and therapy of αvβ3 and NRP‐1 positive tumors, with minimal side effects. Abstract : A novel amphiphilic peptide PA (APPA) containing two functional motifs is designed to coordinate the targeting to integrin αvβ3 and the interaction with neuropilin‐1 on tumor cell membrane . The cooperation of the two motifs fulfills the penetration of the APPA‐based nanosystem deep into the tumor tissue and accumulates there with high specificity and efficacy for enhanced tumor therapy.